Tailoring the electrical properties of MoS2 field effect transistors by depositing Au nanoparticles and alkanethiol molecules. (7th April 2016) - Cho, Kyungjune; Jeong, Hyunhak; Kim, Tae-Young; Pak, Jinsu; Kim, Jae-Keun; Choi, Barbara Yuri; Lee, Takhee
Abstract: We fabricated and characterized MoS2 field effect transistors. First, we measured the electrical properties of MoS2 field effect transistors (FETs) that were made with mechanically exfoliated MoS2 flakes. Then, we deposited Au nanoparticles on the MoS2 channel and measured the electrical properties. We observed whether the source-drain current increased or decreased after the Au particles were deposited. The deposited Au particles either formed an extra current path and increased the current or behaved as charge-withdrawing sites and decreased the current. Next, we deposited alkanethiol molecules on the Au particles to reduce the work function of the Au. Alkanethiol molecules are known to form a self-assembled monolayer on the Au surface, and the electric dipole moment of the molecules causes the work function of the Au to decrease. Au particles can capture electrons from the MoS2 channel due to their high work function. However, the decreased work function of the Au particles subjected to alkanethiol treatment could cause captured electrons to be released from the Au particles to MoS2 . Therefore, the current increased after alkanethiol treatment. This study may provide useful methods to utilize surface treatments with particles and molecules to tailor the electrical properties of MoS2 -based FETs.